Loop Assisted Synchronization-Free Localization for Underwater Acoustic Sensor Networks - Song Zhang; Deshi Li; Lei Li; Zilong Liao (International Journal of Distributed Sensor Networks)
Underwater acoustic sensor networks (UASNs) have attracted significant attention recently. Localization is one of the most important issues associated with UASNs. Most of the existing underwater localization algorithms require time synchronization. However, time synchronization is difficult to be achieved in the underwater networks. The beam width and three-dimensional direction of underwater acoustic sensor nodes are ignored by the existing underwater localization algorithms. This will increase the difficulty to avoid time synchronization. We develop a loop assisted synchronization-free localization to achieve synchronization-free localization algorithm when taking into account the beam width and direction of the underwater nodes. We propose link detection stage to get link state information (symmetry and length). In addition we introduce a loop-assisted localization method to solve the problem of asymmetric link ranging without time synchronization. Finally, we propose an intersections based location estimation mechanism for error problem in practical measurement and we improve the localization accuracy. The simulation results and experimental results verify the effectiveness and feasibility of the proposed work.